Synchronous Rectification Method for CLLC Resonant Converters Based on State-Trajectory Models - Zhenao Sun; Tuanlong Zhang; Chuanpeng Ruan; Qingshuai Yu; Chuxiang Feng (Applied Sciences)
The synchronous rectification (SR) strategy in CLLC resonant converters can effectively enhance operational efficiency, meeting the stringent requirements of application scenarios such as renewable energy systems, DC distribution systems, and electric vehicle-to-grid (V2G) technology. However, due to the complex mathematical model, achieving precise SR directly in CLLC resonant converters is challenging. To realize high-precision and low-complexity SR in CLLC resonant converters, this paper proposes a state-trajectory-based SR strategy. By leveraging geometric principles and tailored simplifications, the expression for SR timing is derived. The proposed SR strategy exhibits excellent versatility and is suitable for the entire frequency range of CLLC resonant converters. The feasibility and accuracy of the proposed SR strategy are validated through an 800 W CLLC resonant converter prototype, demonstrating a robust dynamic performance and achieving a rated efficiency of 97.38%.